Influence of indoor temperature variation on thermal comfort in university classrooms in a tropical Malaysian setting - Mohamad Nur Hidayat, Mat; Amar Ashahmi, Abd Manan; Nurizzatul Atikha, Rahmat; Akrami, Mohamad (EDP Sciences, 2025)
Maintaining a thermally comfortable environment is essential for student well-being and academic performance, especially in regions with consistently high ambient temperatures. The research employs a combination of field measurements and Computational Fluid Dynamics (CFD) simulations to analyse thermal comfort parameters under a range of indoor temperature conditions, from 22 °C to 28 °C. Key indicators such as Predicted Mean Vote (PMV), mean radiant temperature, and operative temperature were evaluated in accordance with ASHRAE 55, ISO 7730, and MS 1525 standards. The results show that PMV values remain within the comfort zone (–0.5 to +0.5) when supply air temperatures are maintained between 22 °C and 24 °C, while values exceed +1.0 at 28 °C, indicating increased discomfort. Zone-by-zone analysis revealed that rear classroom zones experienced higher PMV (up to +1.8), and PMV variability exceeded 0.15 in certain zones, suggesting spatial discomfort. The study also identified a linear increase in PMV with air temperature (R² = 0.91), and the simulated temperatures deviated from experimental measurements by an average of only 0.32 °C. These findings highlight the critical role of precise HVAC temperature control and air distribution in achieving uniform thermal comfort in tropical university classrooms.